ANALISIS STUDI KELAYAKAN USAHA PABRIK TAHU SEBAGAI RESTORAN DI KOTA SALATIGA: ANALISIS STUDI KELAYAKAN USAHA PENGEMBANGAN PABRIK TAHU - Pratama, Otniel Aditya; Uliadi, Tomi; Emanuel, Zefanya (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2023)
A healthy lifestyle is currently a human need to maintain health and fitness, therefore sports facilities and infrastructure are needed by the community. The benoyo tofu factory area is an area that is very suitable for the construction of tofu factory development as a restaurant considering that in the area there are no restaurants of various processed soybeans and restaurants in general for the local community. The aspect that is highlighted and taken into consideration for the construction of the tofu factory as a restaurant is the market aspect. With the combination of quantitative and qualitative data, and descriptive research methods, it is found that the market aspect analysis of the tofu factory development project as a restaurant shows that the tofu factory has the potential to be a restaurant. And this study is feasible to be realized with the hope of improving the welfare and health level of the surrounding community. it is hoped that further research can examine in more detail the development of this tofu factory and for readers the author's hope can be a guide to continue working in the industry.